Premenstrual syndrome: Clinical assessment of treatment outcomes following Borago officinalis extract therapy - Gama, Carlos Romualdo Barboza [UNESP]; Lasmar, Ricardo [UNESP]; Gama, Gustavo Falcão; Oliveira, Lisa; Ribeiro, Márcia Gonçalves; Geller, Mauro; De Oliveira Naliato, Erika Cesar; De Souza Da Fonseca, Adenilson (My University, 2014)
With the objective of evaluating the use of Borago officinalis oil in the treatment of premenstrual syndrome (PMS) symptoms, we assessed 180 patients who presented a clinical diagnosis of PMS and who were treated with one daily 900mg borage oil capsule. Efficacy and safety assessments were performed based on data obtained prior to the start of treatment (Pretreatment), and after each menstrual cycle (Assessment 2-first menstrual cycle after the start of treatment; Assessment 3-second menstrual cycle; Assessment 4/Final Assessment-third menstrual cycle). Efficacy assessments included a PMS questionnaire evaluating emotional and physical PMS symptoms and the Patient and Physician Assessments, in which both the subject and the physician rated the patient's overall condition on a scale of 1-10 points. The primary safety and tolerability measures included any changes in vital signs and physical exam in relation to pretreatment, changes in laboratory exams, and the occurrence of adverse events after the first dose of study medication. We observed a statistically significant reduction in the total scores of the PMS assessment (p<0.0001), with 95.4% of all patients displaying some reduction in scores at Assessment 4 in relation to Pretreatment values. The emotional symptoms and physical symptoms scores also decreased significantly from Pretreatment to Assessment 4 (p<0.0001 for both). In the Patient and Physician Assessments, there was a statistically significant increase in the both the patient's and physician's scores throughout the study in relation to pretreatment values (c2= 328.4; DF= 4; p<0.0001 for Patient Assessment and c2= 355.3; DF= 24; p<0.0001 for Physician Assessment). The majority of the adverse events (AEs) recorded were mild to moderate in intensity, and none were considered serious. The most common AEs were related to the digestive/gastrointestinal tract, specifically stomach/abdominal upset. Physical assessments did not vary significantly throughout the treatment period. Based on the results of this study, we conclude that the use of Borago officinalis oil was safe and effective in the treatment of the physical and emotional symptoms of premenstrual syndrome in the patient population evaluated. © Copyright Moreira Jr. Editora. Todos os direitos reservados.
Keywords: Borage oil; G-linolenic acid; Physical and em otional sym ptoms of prem enstrual syndrome; Prem enstrual syndrome Borago officinalis